Effect of position and size of leaflets on rooting and rhizome formation of ZZ plant (Zamioculcas zamiifolia (Lodd.) Engl.) leaflet cuttings - Thongkham, Leelawadee; Phavaphutanon, Lop (Agriculture and Natural Resources, 2018)
Rooting and rhizome formation was compared of ZZ plant leaflet cuttings taken from the apical, middle,and basal positions of the petiole. Leaflets from each position were propagated as a whole leaflet, an upper half leaflet segment and a lower-half leaflet segment. Whole leaflets from the basal position had greater size and fresh weight than those from the middle and the apical positions, respectively. The upper and the lower half leaflet segments were comparable in size but the lower ones had greater fresh weight. The three cutting types from different positions yielded 90-100% success in rooting and rhizome formation with one small rhizome per cutting on average. However, the root number, root quality score and rhizome size of the whole leaflet cuttings were significantly greater than those of the lower half leaflet segments and the upper ones, respectively. The initial size and fresh weight of cuttings positively correlated with the size of the rhizome produced. The first new shoot produced from the whole leaflet cuttings was larger than that of the lower half leaflet segments and the upper ones, respectively. These results suggested that leaflets taken from the apical, middle and basal positions of the petiole were equally capable of rooting and rhizome formation. An attempt to increase the number of propagules by using leaflet segments was feasible at the expense of a reduced root number per cutting, root quality, size of rhizome and size of a new shoot.